1993
DOI: 10.1085/jgp.102.6.1031
|View full text |Cite
|
Sign up to set email alerts
|

Block by ruthenium red of the ryanodine-activated calcium release channel of skeletal muscle.

Abstract: A B S T R A C T The effects of ruthenium red and the related compounds tetraamine palladium (4APd) and tetraamine platinum (4APt) were studied on the ryanodine activated Ca ~+ release channel reconstituted in planar bilayers with the immunoaffinity purified ryanodine receptor. Ruthenium red, applied at submicromolar concentrations to the myoplasmic side (c/s), induced an all-or-none flickery block of the ryanodine activated channel. The blocking effect was strongly voltage dependent, as large positive potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 49 publications
5
86
0
Order By: Relevance
“…These results suggested that different binding sites are located in the conduction pore of the ryanodine-modified skeletal muscle RyR. Ma (23) did not describe the effects of RR on ryanodine-unmodified RyR1 or RyR2.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…These results suggested that different binding sites are located in the conduction pore of the ryanodine-modified skeletal muscle RyR. Ma (23) did not describe the effects of RR on ryanodine-unmodified RyR1 or RyR2.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, the substates are likely of physiological relevance; however, the dominant mechanism of RR interaction with the Ca 2ϩ -conducting RyRs appears to be full closure. Ma (23) described the effects of RR on the ryanodine-modified skeletal RyR. Several cytosolic RR molecules produced an all-or-none flickery block with a Hill coefficient of 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The (18,19), a derivative Ru360 is a more specific and potent inhibitor of mitochondrial Ca 2ϩ uptake (14,15). At the concentrations and pre-incubation times tested, both RuRed and Ru360 have been shown previously (20) to inhibit significantly mitochondrial Ca 2ϩ uptake in intact cells.…”
Section: Cch-and Insp 3 -Evoked Ca 2ϩ Signals Are Significantly Slowementioning
confidence: 99%
“…One type, e.g. ruthenium red [4,5], directly blocks the ryanodine receptor (RyR)/Ca 2÷ channel [6][7][8]. The other type, e.g.…”
Section: Introductionmentioning
confidence: 99%